2009
DOI: 10.2478/v10140-009-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Frequent aberrant expression of p53 protein in gliomas but not in capillary hemangioblastomas and pheochromocytomas

Abstract: Background. Glioma is the most common and deadly malignancy of the central ner vous system. Capillary hemangioblastoma (CHB) is a rare and usually benign tumour of brain, occurring as part von Hippel-Lindau (VHL) disease or as a sporadic entity. For an improved understanding of the molecular mechanisms of the pathogenesis of VHL-related tumours and gliomas, we analysed the expression of the tumour suppressor proteins p53 and p16, and promoter methylation of the tumour suppressor genes (TSGs) MGMT and RASSF1A.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…ARF, encoded by p14, is a protein of the p53-regulated pathway. When the results of our previous study (8) were considered in combination with the present data, we noted an exclusive nature of the occurrence of p53 alterations and p14 hypermethylation. In PCC and CHB, where no aberrant expression of p53 was detected by means of immunohistochemistry, aberrant methylation of p14 was a frequent event that occurred in 44% of cases.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…ARF, encoded by p14, is a protein of the p53-regulated pathway. When the results of our previous study (8) were considered in combination with the present data, we noted an exclusive nature of the occurrence of p53 alterations and p14 hypermethylation. In PCC and CHB, where no aberrant expression of p53 was detected by means of immunohistochemistry, aberrant methylation of p14 was a frequent event that occurred in 44% of cases.…”
Section: Discussionsupporting
confidence: 76%
“…In gliomas, 14 out of 15 cases with the genetic or epigenetic inactivation of p16 had also reduced the expression of the p16 protein. Interestingly, all cases with CHB and PCC showed a reduced or no p16 staining in our previous study (8), despite DNA methylation or mutation status, showing the importance of additional regulators for the p16 expression in these tumours. Similarly, the study of Muscarella et al (6) showed a reduced p16 expression in all but one cases with PCC, while the genetic and epigenetic alterations occurred only in a set (68%) of the cases.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations